Kebijakan Keselamatan Dan Keamanan Maritim Dalam Menunjang Sistem Transportasi Laut - Arifian, Naf'an; Putra, Riki Wanda; Alhafidh, Nabil Ikhsan (Politeknik Pelayaran Sumatera Barat, 2025)
The research aims to analyze maritime safety and security policies in supporting the maritime transportation system. This research uses a descriptive method, because the data collected are in the form of words, images, and not numbers. The data comes from interview scripts, field observations/notes, Focus Group Discussions, videotapes, photographs, notes or memos, and other official documents. Data analysis uses an ethical and emic approach and a triangulation process. Informant determination uses a purposive technique. Research result: Maritime transportation in Indonesia has not yet developed optimally, but has strong potential to be developed, considering its characteristics of being able to carry out mass transportation. Therefore, the safety and security system is a key factor that must be considered and as a basis and benchmark for decision making. The safety and security system for maritime transportation in Indonesia has not been running optimally, accidents still often occur both due to natural factors and human factors. Government policies in the maritime sector, both the fishing industry and the shipping industry have not been implemented consistently in accordance with applicable laws. So far, the development of maritime potential has been hampered by structural problems, and there has been no national political awareness of the magnitude of the economic, fisheries and maritime potential.